Contemporary issues and challenges faced by the takaful industry in Malaysia - Zakariyah, Habeebullah; Ahmed, Alinasser Abdirasak (Al Hikmah Research and Publication Centre, 2019)
This paper examines the contemporary issue faced by the Islamic insurance (takaful) industry in Malaysia. The paper will then try to highlight the Shariah issues in the current practice of the takaful industry and takaful products. Therefore, the paper tries to critically analyses previous articles regarding the topic of takaful. Moreover, the paper would be a useful reference for any researcher who is researching the Shariah issues relating to takaful. Besides, the result of the paper would provide insight into how the Malaysian takaful industry and the takaful industry globally could improve their business operation model. However, the finding may be limited because the paper only concentrates on the Malaysian takaful industry